2011
DOI: 10.3233/jvr-2011-0548
|View full text |Cite
|
Sign up to set email alerts
|

Understanding employers' hiring intention in relation to qualified workers with disabilities

Abstract: The present study focused on the intentions of employers to reach out toward qualified workers with disabilities as part of their hiring pool recruitment activity. An employer survey was developed in accord with the theory of planned behavior (Ajzen, 2005). According to the tenets of the model, it was hypothesized that through multiple regression, it would be demonstrated that employer attitudes, subjective norms, and perceived control variables predict the intention to engage in hiring behavior toward qualifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 0 publications
8
55
1
3
Order By: Relevance
“…The research findings corroborated with Ang et al (2015) and Kluge and Krings (2008) in that attitudes and subjective norm were strong predictors in TPB. Furthermore, the present findings were in line with and supported Lu et al (2011) andFraser et al (2011) in that attitude was significance contributor to the prediction of hiring. Subjective norm and past experience also supported Lu et al (2011) where they were found to be significant to the intention prediction.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The research findings corroborated with Ang et al (2015) and Kluge and Krings (2008) in that attitudes and subjective norm were strong predictors in TPB. Furthermore, the present findings were in line with and supported Lu et al (2011) andFraser et al (2011) in that attitude was significance contributor to the prediction of hiring. Subjective norm and past experience also supported Lu et al (2011) where they were found to be significant to the intention prediction.…”
Section: Discussionsupporting
confidence: 89%
“…In Hypothesis 2, subjective norm was found to have relationships to managers' intention to hire older workers. The results were supportive of Ang et al (2015), Fraser et al (2011), andLu et al (2011) respectively where subjective norm was a great contributor to intention.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations